2005
DOI: 10.1364/ao.44.001879
|View full text |Cite
|
Sign up to set email alerts
|

Computational calibration method for optical tomography

Abstract: We propose a computational calibration method for optical tomography. The model of the calibration scheme is based on the rotation symmetry of source and detector positions in the measurement setup. The relative amplitude losses and phase shifts at the optic fibers are modeled by complex-valued coupling coefficients. The coupling coefficients can be estimated when optical tomography data from a homogeneous and isotropic object are given. Once these coupling coefficients have been estimated, any data measured w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…(9) computationally, it may, for example, be written in a weak formulation and implemented on a discretized mesh using the finite element method. 28,29 When there is no scattering, Eq. (9) reduces to ðŝ · ∇ þ μ a Þϕ ¼ q.…”
Section: Radiative Transfer Equationmentioning
confidence: 99%
“…(9) computationally, it may, for example, be written in a weak formulation and implemented on a discretized mesh using the finite element method. 28,29 When there is no scattering, Eq. (9) reduces to ðŝ · ∇ þ μ a Þϕ ¼ q.…”
Section: Radiative Transfer Equationmentioning
confidence: 99%
“…If the coupling coefficients ζ 0 are not estimated by the pre-calibration techniques [5,6,9,10], they are typically fixed to the ideal "no losses" values, i.e., ε 1 (ζ 0 ) ≡ 0. In addition, if the random measurement errors have zero mean (ē = 0), the MAP estimate (18) has the usual form…”
Section: Statistical Inversion In Dotmentioning
confidence: 99%
“…There are also other uncertain model parameters such as coupling coefficients that include source strength, coupling losses of the optodes and detector efficiency or gain. It has previously been observed that small errors in source and detector positions and coupling coefficients can cause large artifacts in the reconstructed images [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviews which refer to TV include [Kaipio and Somersalo, 2005;Vogel, 2002] whereas DOT studies include [Kolehmainen et al, 2000;Paulsen and Jiang, 1996;Tarvainen et al, 2005a]. …”
Section: Edge Preserving Regularizationmentioning
confidence: 99%